2022
DOI: 10.1177/15266028221127839
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of EndoAnchors on Aneurysm Sac Regression for Patients Treated With Infrarenal Endovascular Repair With Hostile Neck Anatomies: A Propensity Scored Analysis

Abstract: Purpose: To analyze sac evolution patterns in matched patients with hostile neck anatomy (HNA) treated with standard endovascular aneurysm repair (sEVAR) and endosutured aneurysm repair (ESAR). Methods: Observational retrospective study using prospectively collected data between June 2010 and December 2019. ESAR group data were extracted from the primary arm of the PERU registry with an assigned identifier (NCT04100499) at 8 centers and those from the sEVAR came from 4 centers. Suitability for inclusion requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Also, adjunctive procedures to standard EVAR may be useful to prevent PND and other proximal neck complications. An observational study comparing patients with hostile PAN treated with standard EVAR vs. endosutured aneurysm repair (ESAR) concluded that the use of EndoAnchors increased the rate of sac regression ( p = 0.003) and reduced the number of type IA endoleaks ( p = NS) [ 41 ]. However, this study did not provide any direct measurement of PAN evolution and/or PND; thus, any inferences as to whether the use of EndoAnchors may halt the process leading to neck enlargement remain purely speculative at this time.…”
Section: Discussionmentioning
confidence: 99%
“…Also, adjunctive procedures to standard EVAR may be useful to prevent PND and other proximal neck complications. An observational study comparing patients with hostile PAN treated with standard EVAR vs. endosutured aneurysm repair (ESAR) concluded that the use of EndoAnchors increased the rate of sac regression ( p = 0.003) and reduced the number of type IA endoleaks ( p = NS) [ 41 ]. However, this study did not provide any direct measurement of PAN evolution and/or PND; thus, any inferences as to whether the use of EndoAnchors may halt the process leading to neck enlargement remain purely speculative at this time.…”
Section: Discussionmentioning
confidence: 99%